THE WORK OF MADURESE CULTURE IN BUSINESS ACTIVITIES - Nur Syakherul Habibi; Mohammad Amiruddin; Ukhti Raudhatul Jannah (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to investigate the work of madurese culture in business activities. The research population comprised all the employees and the employers. A sample was established using random sampling technique. This study is an ex post facto research, using quantitative approach. The data were analyzed by simple regression technique. Observation and interview are conducted to get the data. The results show that the work of madurese culture in business activities is positive and significant, and the amount of the role of the variable is 0.579 (57.9%). The application of appropriate culture, religion, practices, etc. by the traders assists in the smooth operation of the offered goods. The culture of the traders being engaged helps the customers get good service and high-quality products. It suggests that the merchants should adopt the proper mentality in order to create the ideal conditions for good service. Moreover, customers benefit from the trading culture by receiving good service and high-quality items. It implies that traders should have the correct mindset in order to establish the optimal conditions for providing excellent service. Keywords: Activitiy, Business, Culture, Madurese, Work